Assessing the Impact of Mobile-Based Training on Teachers’ Achievement and Usage Attitude - Dahri, Nisar Ahmed; Vighio, Muhammad Saleem; Omar A. Alismaiel; Waleed Mugahed Al-Rahmi (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Teachers’ professional development plays a key role in imparting quality education. However, the design and delivery of quality professional development programs is a challenging problem due to numerous issues such as inadequate policies, lack of skilled personnel and training, politically influenced appointments, and dependency on the traditional modes of training. The COVID-19 pandemic has further escalated the situation and severely affected trainers’ and trainees’ interest, motivation, and engagement. Due to its ubiquitous, flexible, and cost-effective nature, technology has played a key role in carrying out educational activities even in the pandemic situation. However, little emphasis has been provided on the use of technology for the professional development of teachers. This study investigates the effects of mobile-based training app on teachers learning outcomes and attitudes towards its usage. The training app is based on our enhanced CPD model for teachers’ professional development. For the study, 308 in-service elementary school teachers of division shaheed Benazirabad are selected for the training and assessment purposes. To perform the experiments, teachers were divided into two groups: experimental and control. The experimental group contained 158 teachers which were provided training through the mobile app. The remaining 150 teachers of the control group were provided training using the traditional physical appearance. Pre and post-test were designed to examine the effects of mobile-based training on the teachers’ learning outcomes before and after the training intervention. Besides assessing the learning outcomes, the attitude towards the use of the training app was also assessed using the attitude scale. The analysis of results determined that the training through a mobile app has a significant effect on teachers learning outcomes in terms of knowledge, skills, and dispositions. Furthermore, teachers showed a positive attitude towards the use of training app. The experimental group had significantly high attitude scores in post-test toward mobile-based training systems. Teachers’ experience using the mobile app has been perceived as an approach that has significantly increased teaching proficiency. Experimental results suggest that mobile-based professional development modes positively impact teachers’ professional and academic achievement and performance to produce a rising number of certified teachers irrespective of time, space, and financial constraints.